Chromophore structure in a long-lived intermediate of heliorhodopsins : switching of a hydrogen bonding partner of protonated Schiff base - Urui, Taito (2020)
Heliorhodopsin (HeR) is a novel class of retinal proteins discovered in 2018 [1]. HeR contains an all-trans-retinal as a chromophore, which is covalently bound to a lysine residue through a protonated Schiff base linkage. Although amino acid sequences of HeR are largely different from those of type-1 rhodopsins, a family of HeR shares the seven-transmembrane helix motif. Photoexcitation of the all-trans-retinal chromophore results in isomerization to a 13-cis form. This isomerization initiates a photocycle involving a series of intermediates, which are similar to those observed for type-1 rhodopsins. HeR has a long-lived intermediate in its photocycle, which is named the O intermediate, suggesting that the function of HeR is light sensing. In order to understand the functional role of the O intermediate, we investigated the chromophore structure in two HeRs, HeR 48C12 and T. archaeon HeR, using time-resolved resonance Raman spectroscopy.